Analisis Keputusan Pembagian Dividen yang Dipengaruhi oleh Investment Opportunity Set, Free Cash Flow, Kebijakan Hutang dan Collateralizable Assets - Agris Haryanto Prakasa; Agus Munandar (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2022)
The background of this study is begins with the high intensity of competition that occurs in go public companies in the Bursa Efek Indonesia. The purpose of this study is to find out the amount of dividends distributed by the company and find out what factors affect the distribution of company dividends. Samples used in this study are obtained 20 companies, the company's sample consists of secondary data collected for data processing. 20 companies are samples that selected from index LQ45 population and constantly listing in index LQ45 since 2018-2020. The process of data processing using statistica tools Eviews-10. The final result of this study are simultaneously IOS, FCF, Leverage, and CA has significant affect to dividend policy; while the variable of leverage has negative affect but IOS, FCF, CA has no affect toward the dividend policy.